From Legal Frameworks to Field Implementation: Developing and Evaluating a Participatory Rights-Based Toolkit for GBV Prevention in Humanitarian Crisis Settings - Portia Ozioma Chigbu; Iyanuoluwa Abolarinwa; Dorcas Owusua; Toyosi Motilola Olola; Motunrayo Tolani Omidiora (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Humanitarian crisis settings; encompassing natural disasters, armed conflicts, and displacement; create environments of acute vulnerability in which gender-based violence (GBV) intensifies and legal protections for women are often inaccessible. This paper presents the design and critical evaluation of a modular, rights-based toolkit aimed at preventing GBV and promoting gender equality in such contexts. Building on a participatory needs assessment with local stakeholders, the methodology integrates domestic statutes, customary laws, and international norms into user-friendly modules. An iterative drafting and pilot-testing cycle in Mozambique and among displaced populations in Ethiopia and Colombia refined the toolkit’s legal, cultural, and logistical components. Validation metrics, usability, cultural relevance, and legal robustness; demonstrated notable improvements: legal-aid inquiries rose by 35 percent, identification rates of survivors increased to 65 per cent in Mozambique and 45 percent in Colombia, and interagency coordination was strengthened through blended in-person and mobile delivery. Despite these successes, resource constraints and legal pluralism pose challenges to scaling and sustainability. The discussion highlights strategies for institutionalization, including integration within national disaster-risk frameworks, multi-stakeholder partnerships, and ongoing capacity building. The paper concludes with recommendations for embedding the toolkit in humanitarian coordination mechanisms and outlines avenues for future research on long-term impact and digital adaptations.